2010
DOI: 10.1088/0026-1394/47/1a/01007
|View full text |Cite
|
Sign up to set email alerts
|

Final report on CCEM.RF-K4.CL comparison: RF-voltage measurements up to 1 GHz

Abstract: We report the results of an international comparison of measurements of radio frequency voltage in the frequency range 1 MHz to 1 GHz. This comparison was performed as a Key Comparison under the auspices of the Consultative Committee for Electricity and Magnetism (CCEM) of the International Committee for Weights and Measures (CIPM). Participating laboratories were the designated national metrology institutes (NMIs) for their respective countries.Main text. To reach the main text of this paper, click on Final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In comparison to the traveling standards in the CCEM.RF-K4.CL key comparison [10], the evaluated results for the NRC CTVC up to 1 GHz look encouraging. However, to be a reliable reference standard for RF-DC difference up to 1 GHz, further investigations for the CTVC are still required.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In comparison to the traveling standards in the CCEM.RF-K4.CL key comparison [10], the evaluated results for the NRC CTVC up to 1 GHz look encouraging. However, to be a reliable reference standard for RF-DC difference up to 1 GHz, further investigations for the CTVC are still required.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, comparing the results shown in Fig. 5 to the results evaluated by NMC, A*STAR for traveling standards in the key comparison CCEM.RF-K4.CL [10], it is found that the working frequency range of the CTVC designed by NRC could be extended up to 1 GHz. Furthermore, if reversely using (15) and (11), the RF-DC difference δ at the middle of the tee of a CTVC could be transferred to the calibration factor K of a power sensor.…”
Section: Performance Evaluation Of the Nrc Ctvc For Rf-dc Transfermentioning
confidence: 85%
See 1 more Smart Citation